PENGARUH MODEL PEMBELAJARAN KOOPERATIF MAKE A MATCH TERHADAP HASIL BELAJAR GEOGRAFI PESERTA DIDIK PADA MATERI KEBENCANAAN DI SMAN 5 PADANGSIDIMPUAN - Nailan Maulida Rizka; Bigharta Bekti Susetyo (Ensiklopedia of Journal, 2026)
This study seeks to examine the impact of the Make a Match Cooperative Learning model on the geography learning outcomes of eleventh-grade social science students at SMAN 5 Padangsidimpuan regarding Disaster Management content. A quantitative methodology employing a quasi-experimental design (non-equivalent control group design) was utilized. The sample comprised 25 students from class XI-7 (experimental group) and 25 students from class XI-6 (control group). The Independent Sample t-test revealed a t-count for the Posttest of 6.433 and an N-Gain of 7.001, both exceeding the t-table value of 2.011 (Sig. = 0.000 0.05), leading to the rejection of H₀ and acceptance of H₁. The experimental class exhibited a higher average N-Gain (0.6728, medium category) compared to the control class (0.3787). Consequently, the Make a Match Cooperative Learning model significantly impacts geography learning outcomes at SMAN 5 Padangsidimpuan.Keywords: Make a Match, Geography Learning Outcomes, Cooperative Learning, Disaster Management, Quasi-Experiment